(untitled) (Faridpur Medical College Journal, 2026)
Background: The vertebral column is the central bony pillar of the body. With the development of vertebral surgery and biomechanics as well as the improvement of recognition in vertebral column diseases, the overall anatomic data are needed to be provided. The data can be useful while carrying out surgical procedures with the help of model vertebral column in the operation theatre. Materials and Methods: This cross-sectional study was carried out with an attempt to construct data on the length of the transverse process of fully ossified dry human fifth lumbar vertebrae in the Department of Anatomy, Sir Salimullah Medical College, Dhaka, from January 2012 to December 2012. In this study, a total of 153 morphologically normal complete bones of unknown sex were included. Sexes of the collected bones were determined. Results: This study observed that the mean + SD value of transverse process length of 153 fifth lumbar vertebrae were 29.1 + 2.3 mm in male and 27.8 + 2.5 mm in female on left and 27.9 + 2.4 mm in male and 26.0 + 2.3 mm in female on right side. All values were significantly higher in male than that of female. Conclusion: The results of the present study provide useful information for safe surgery of posterior segmental screw fixation & for the development of new spinal implant system. Faridpur Med. Coll. J. 2026;21(2): 34-37